2023
DOI: 10.1021/jacs.2c08636
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Enzymes: Phosphate-Binding Polypeptides Mediate Phosphoryl Transfer to Synthesize Adenosine Triphosphate

Abstract: Reactions involving the transfer of a phosphoryl (−PO3 2–) group are fundamental to cellular metabolism. These reactions are catalyzed by enzymes, often large and complex, belonging to the phosphate-binding loop (P-loop) nucleoside triphosphatase (NTPase) superfamily. Due to their critical importance in life, it is reasonable to assume that phosphoryl-transfer reactions were also crucial in the pre-LUCA (last universal common ancestor) world and mediated by precursors that were simpler, in terms of their seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…At the same time, the work clearly demonstrates that all considered cases are based on the common β-α-β motif (also described as a closed loop ( Berezovsky et al, 2000 ; Berezovsky and Trifonov, 2001a ; Berezovsky and Trifonov, 2001b ; Berezovsky et al, 2002 ) or supersecondary structure element ( Levitt and Chothia, 1976 )) dominated by Gly ( Trifonov, 1999 ) and few other ancient amino acids ( Trifonov, 2000 ), allowing one to hypothesize the common origin of all phosphate binding elementary functions in the whole diversity of contemporary proteins. One of the most recent works inspired by Dan Tawfik and finished by his colleagues further supports this hypothesis, unraveling the key role of the phosphoryl transfer as a fundamental reaction in the cellular metabolism existing from the origin of enzymes ( Vyas et al, 2023 ). The whole spectrum of elementary functions with a detail description of the biding specifics of all components of (di)nucleotide-containing ligands is accumulated in the nucleotide binding database (NBDB, https://nbdb.bii.a-star.edu.sg ( Zheng et al, 2016 ),), which became an inspiration and reliable data source for a number of works exploring the evolution, function, and design potential of the (di)nucleotide-containing ligand binding ( Heizinger and Merkl, 2021 ; Nepomnyachiy et al, 2017 ; Yin et al, 2021 ; Longo et al, 2020a , 2020b , 2022b ; Chu and Zhang, 2020 ; Kolodny, 2021 ; Romero-Romero et al, 2021 ; Narunsky et al, 2020 ; Bhagavat et al, 2017 ).…”
Section: Function From Fragments: From the Start In Prebiotic World T...mentioning
confidence: 86%
See 3 more Smart Citations
“…At the same time, the work clearly demonstrates that all considered cases are based on the common β-α-β motif (also described as a closed loop ( Berezovsky et al, 2000 ; Berezovsky and Trifonov, 2001a ; Berezovsky and Trifonov, 2001b ; Berezovsky et al, 2002 ) or supersecondary structure element ( Levitt and Chothia, 1976 )) dominated by Gly ( Trifonov, 1999 ) and few other ancient amino acids ( Trifonov, 2000 ), allowing one to hypothesize the common origin of all phosphate binding elementary functions in the whole diversity of contemporary proteins. One of the most recent works inspired by Dan Tawfik and finished by his colleagues further supports this hypothesis, unraveling the key role of the phosphoryl transfer as a fundamental reaction in the cellular metabolism existing from the origin of enzymes ( Vyas et al, 2023 ). The whole spectrum of elementary functions with a detail description of the biding specifics of all components of (di)nucleotide-containing ligands is accumulated in the nucleotide binding database (NBDB, https://nbdb.bii.a-star.edu.sg ( Zheng et al, 2016 ),), which became an inspiration and reliable data source for a number of works exploring the evolution, function, and design potential of the (di)nucleotide-containing ligand binding ( Heizinger and Merkl, 2021 ; Nepomnyachiy et al, 2017 ; Yin et al, 2021 ; Longo et al, 2020a , 2020b , 2022b ; Chu and Zhang, 2020 ; Kolodny, 2021 ; Romero-Romero et al, 2021 ; Narunsky et al, 2020 ; Bhagavat et al, 2017 ).…”
Section: Function From Fragments: From the Start In Prebiotic World T...mentioning
confidence: 86%
“…The common origin of this elementary function was discussed from the perspective of both structure and function, pointing to β-α-β closed loop ( Berezovsky et al, 2000 , 2017b ; Berezovsky and Trifonov, 2001a ) as a potential first structural carrier of the short phosphate binding signature ( Goncearenco and Berezovsky, 2010 , 2015 ; Longo et al, 2020b ), which is still detectable in modern proteins ( Berezovsky, 2019 ; Goncearenco and Berezovsky, 2012 ; Schneider et al, 2006 ; Laurino et al, 2016 ; Longo et al, 2020a ). It was also shown that phosphate binding became an element of diverse biochemical function, contributing weak helicase activity ( Vyas et al, 2021 ), providing transfer of the phosphoryl group ( Vyas et al, 2023 ), and being complemented by other elementary functions ( Berezovsky et al, 2003a , 2003b ; Gruic-Sovulj et al, 2022 ; Longo et al, 2022b ). Based on numerous works illuminating the sequence/structure determinants, enzymatic and other biochemical reactions it is part of, we reconstructed the most ancient, simplest, and versatile prototype from which this elementary function apparently started.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggests, however, that many contemporary proteins condensed around relatively short 'seeding' peptides with simple secondary structures. [14][15][16][17][18][19][20][21][22] These evolutionary nucleidespite billions of years of evolutionhave remained largely unchanged on account of their profound functional importance.…”
Section: Introductionmentioning
confidence: 99%